1978
DOI: 10.1139/y78-031
|View full text |Cite
|
Sign up to set email alerts
|

Enkephalin and substance P effects related to trigeminal pain

Abstract: Iontophoretic applications of enkephalin (20-150 nA) reduced the spontaneous firing frequency of nociceptive neurons in the trigeminal nucleus caudalis of decerebrated cats. The response evoked by noxious stimulation (tooth pulp) was gradually inhibited during the 1st minute of application of the opioid and generally remained depressed for 5 min after the current was turned off. These effects of enkephalin were blocked by intravenously or iontophoretically administered naloxone. Nonnociceptive neurons or nocic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Although these experiments do not entirely exclude a postsynaptic site of action, for instance on an interneuron in the substantia gelatinosa, they are most easily explained by a selective presynaptic block of transmitter release from nociceptive afferents. A similar differential effect of enkephalin on responses of nucleus caudalis neurons in the trigeminal nucleus to tooth pulp stimulation was fo und by Andersen et al (1978). In spinal cord explants with attached sensory dorsal .toot ganglia, sensory-, J evoked synaptic activity in the dorsal horn region, but not in the ventral horn· region, is blocked by opiates and opioid peptides, and this effect is prevented by naloxone (Crain et aI1977, 1978.…”
Section: Association Of Opiate Action With Nociceptive Afferentsmentioning
confidence: 79%
“…Although these experiments do not entirely exclude a postsynaptic site of action, for instance on an interneuron in the substantia gelatinosa, they are most easily explained by a selective presynaptic block of transmitter release from nociceptive afferents. A similar differential effect of enkephalin on responses of nucleus caudalis neurons in the trigeminal nucleus to tooth pulp stimulation was fo und by Andersen et al (1978). In spinal cord explants with attached sensory dorsal .toot ganglia, sensory-, J evoked synaptic activity in the dorsal horn region, but not in the ventral horn· region, is blocked by opiates and opioid peptides, and this effect is prevented by naloxone (Crain et aI1977, 1978.…”
Section: Association Of Opiate Action With Nociceptive Afferentsmentioning
confidence: 79%
“…Physiological studies have shown that much of the ENK inputs to dorsal horn neurons exert their influence postsynaptically (Miletic and Randic, 1981;Willcockson et al, 1984;Zieglgansberger and Tullock, 1979). This input affects a wide range of cell types, as indicated by its nonspecific inhibitory influence on the transmission of non-noxious as well as noxious stimuli through the dorsal horn of the spinal cord (Andersen et al, 1978;Duggan et al, 1977;Henry et al, 1980). It has been suggested that a substrate for such modality-nonspecific effects is the presence of ENK axosomatic innervation onto second-order neurons, which is a n effective regulator of all transmissions arising more distally on the dendrite (Ruda et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The processes of these neurons are unmyelinated and have a distribution similar to that ofpain sensory fibers in the spinal cord and in the brainstem (30)(31)(32)(33). Substance P is released in the spinal cord by stimulation of sensory nerves (34,35), and substance P applied iontophoretically increases the activity ofneurons in the spinal cord and brainstem that receive input from pain sensory neurons (36)(37)(38). The evidence that substance P is a transmitter for certain pain sensory neurons has been reviewed (19).…”
Section: Neuronsmentioning
confidence: 99%